LYSIMETER - A UNIQUE TOOL FOR MONITORING THE INTERACTIONS AMONG THE COMPONENTS OF ENVIRONMENT - Matušek, Ivan; Reth, Sascha; Heerdt, Christian; Hrčková, Katarína; Gubiš, Jozef (Proceedings of National Aviation University (archive), 2016)
Modern lysimeter facilities in connection with meteorological stations allow monitoring and evaluation of mutual basic components of the environment, such as water, air, soil and vegetation. Water is the most important component of the ecosystem and the component which connects all the other components. Therefore, we need to know the basic distribution and water balance in the different components of the environment to be able to interpret some processes in nature. Rainfall, which is the primary source of vital processes in the soil, is formed in the air. The amount of precipitation that gets into the soil and into the groundwater is affected by weather conditions. Primary distribution of rainwater is divided between infiltration, surface runoff, transpiration and evapotranspiration. The amount of water infiltrated into the soil and then evaporated by solar activity or activities of plants can be identified primarily by monitoring changes in weight. For this monitoring we use weighable lysimeter. This equipment with the monolith size of surface area 1 m2 and the depth of 1.5 m is able to follow online updates of weight of the 2 ton body with an accuracy of 100 g. When we add to quantification of leakages through the bottom layer, we obtain a comprehensive record of rainfall at the time in the natural environment of the individual components. The obtained data can be further interpreted in terms of the needs of hydrology, agriculture, and environmental studies, and according to the purpose and objectives for which we want to use them.